Occupation Change of Farmer to Fishermen: A case in Coastal Rural Area in Gunungkidul District - Ritohardoyo, Su (Forum Geografi, 2002)
Utilization of marine resource is one of type of farmer coping with critical land in coastal 47% The consequence of this, is the change in their occupation status from the farmer to ï¬sherman However the change does not always mains that their poverty status may also changes. This factual problem is the base for research objectives, with the main emphasis on understanding farmer motives of changing occupation to fisherman, process variation of occupation change, and the impact of this process to household incomeThe research was carried out in six coastal village of Gunungkidul Distric. Survey method was employed by collecting data from respondents. The population of respondents amounted to 341 households (HH) working as ï¬sherman Sampling technique was proportionally simple random in which 120 HH was taken as mpondents sample. They were representazivis of Kanigoro, Pucung, Kemadang, Ngestiharjo, Sidoharjo, and Purwodadi villages. Data on socio economic structure of the household, the process of occupation change, and household income were collected by mean of structured interview. Data analysis was performed through descriptive technique in which frequencies and cross tabulation were mostly used.The research results indicate that the motive of local farmer to become fisherman are various, but the main motive (81,7%) to increase household income. The major cause of this is physical environment pressure of the area (ie. critical land and backward village). This leads ï¬irmer to low level of accissebility to socio-economic inï¬asructure, and low level of economic status or very poor category. The majority of farmer (58,3%) carried out transitional occupation beï¬are becoming ï¬sherman. This encompass activities as ï¬shing or collecting sea shell and lsea algaemn the sea front Intermediary activitis being perï¬mned a form of adaptation to marine environment (sea water) from agricultural land environment. This means that most farmers search and gain skill and experiences related to fishery. Occupation change from farmer to ï¬sherman has significant impact in the betterment of income. In average, the ï¬sherman monthly income is Rp 531,375 which is much higher than the minimum level of basic need in Yogyakarta Povince (Rp 266,870.). In the other word the occupation change from farmer to ï¬sherman driven by motive to increasses household income is proven to be capable to statisfy the need if household economy.